The molecular mechanisms of signal pathway activating effect of E2F-1/NF-κB/GSK-3β on cognitive dysfunction of Alzheimer rats. Issue 2 (20th December 2021) - Tuerxun, Mayila; Muhda, Ajar; Yin, Lixin
ABSTRACT: Alzheimer disease (AD) seriously harms human health and its onset is insidious. Therefore, it is of great significance to find out the pathogenesis of AD disease for improving the prevention and treatment effect of the disease. The study drew attention to the influence of E2F-1/NF-κB/GSK-3β signaling pathway on cognitive dysfunction of Alzheimer rats. 60 specific pathogen-free (SPF) SD rats were selected as research subjects. The, the AD model was created by injecting Aβ1-42 into hippocampus CA1 region of AD rats using a microscopic syringe. Besides, Morris water maze test and Western blot were performed to detect the cognitive function, the levels of destination protein and active oxidation products in the brain of rats. Compared to the Sham group, the escape latency and the distance of the model group significantly increased ( P <  0.05), and the number of times to pass the target quadrant was significantly reduced ( P <  0.05); the expression levels of E2F-1 and NF-κB protein in the hippocampus and the phosphorylation levels of Tau231, Tau262, Tau396, Tau404 and T216-GSK-3β protein of the model group were significantly increased ( P <  0.05); the ROS/RNS value in the hippocampus of the model group significantly increased ( P <  0.05). AD model rats exhibit obvious cognitive dysfunction, which is associated with the activation of E2F-1/NF-κB/GSK-3β signaling pathway and the heightened Tau protein phosphorylation level.